A Data Association Method for Vehicle Detection Based on Millimeter Wave Radar. (May 2020) - Li, Chuan; Luo, Feng
Abstract: This paper proposes a vehicle object assoication method based on millimeter wave radar detection, which can improve the accuracy of driving assistance functions that take vehicle targets as input. This method is used to judge the data association of the target tracking group through Kalman filtering. The L-shaped model is used to initially determine the outline of the measurement object, and the close object clusters are segmented according to the standard vehicle parameters and the related speed. Furthermore, a Gate algorithm is used to associate the hypothetical object within a certain area with the target. Road test experiments show that the data assoiation method has high accuracy for detected vehicles.